MODERN ANALYTICAL APPROACHES TO THE DETERMINATION AND REMOVAL OF HEAVY METAL IONS FROM AQUEOUS MEDIA (International journal of artificial intelligence, 2026)
Introduction. The intensive development of industry, urbanization, and the growth of technogenic load have led to a significant increase in the concentration of heavy metal ions in natural and wastewater. These pollutants are characterized by high chemical resistance, the ability to accumulate bio, and a pronounced toxic effect on biological systems, which determines their particular ecological and sanitary hazard [1,2]. Unlike organic compounds, heavy metals do not undergo biodegradation and can circulate in the environment for a long time, transitioning from one ecosystem to another.